2015
DOI: 10.1098/rsif.2015.0461
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic drag constrains head enlargement for mouthbrooding in cichlids

Abstract: Presumably as an adaptation for mouthbrooding, many cichlid fish species have evolved a prominent sexual dimorphism in the adult head. Since the head of fishes serves as a bow during locomotion, an evolutionary increase in head volume to brood more eggs can trade-off with the hydrodynamic efficiency of swimming. Here, the differences between males and females in threedimensional shape and size of the external head surfaces and the effect thereof on drag force during locomotion was analysed for the Nile tilapia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…AI treatment also had some further effects on the overall appearance of the treated fish impacting body and head shape. Previous studies showed that the sexes in cichlids differ mostly in head shape and that mouth-brooding females have larger heads (buccal region) with longer snouts [Oliveira and Almada, 1995;Herler et al, 2010;Van Wassenbergh et al, 2015]. This is in accordance with our findings that females have a more slender but longer head with a shorter mouth, whereas males have a deeper body, a shorter head, as well as longer dorsal and anal fins.…”
Section: Discussionsupporting
confidence: 83%
“…AI treatment also had some further effects on the overall appearance of the treated fish impacting body and head shape. Previous studies showed that the sexes in cichlids differ mostly in head shape and that mouth-brooding females have larger heads (buccal region) with longer snouts [Oliveira and Almada, 1995;Herler et al, 2010;Van Wassenbergh et al, 2015]. This is in accordance with our findings that females have a more slender but longer head with a shorter mouth, whereas males have a deeper body, a shorter head, as well as longer dorsal and anal fins.…”
Section: Discussionsupporting
confidence: 83%
“…Alternatively, body depth could be the result of correlated selection on pectoral fin morphology, but still provide a performance benefit such as in swimming abilities. This type of correlational selection could potentially facilitate rapid adaptation to particular hydrodynamic regimes where a more streamlined body and smaller fins would be advantageous (Higham, ; Van Wassenbergh, Potes, & Adriaens, ). Because correlated selection provides multiple simultaneous targets for selection, this type of integration has been suggested to play a role in the rapid evolution of structures like jaws, teeth, and a number of other traits in cichlids and other adaptively diverging groups (Albertson, Streelman, Kocher, & Yelick, ; Hulsey, Machado‐Schiaffino, et al, ; Husemann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Buccal volume is in turn limited by gill size related to requirements for respiratory function (O'Connor, Reardon, & Chapman, ). Mouthbrooding capacity has also been linked to diet and head shape in haplochromine cichlids (Van Wassenbergh, Potes, & Adriaens, ; tkint, Verheyen, De Kegel, Helsen, & Adriaens, ). There is evidence that A. calliptera shows substantial differences in trophic resource use and head shape across its geographic range (P. Parsons, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Buccal volume is in turn limited by gill size related to requirements for respiratory function (O'Connor, Reardon, & Chapman, 2012). Mouthbrooding capacity has also been linked to diet and head shape in haplochromine cichlids (Van Wassenbergh, Potes, & Adriaens, 2015;tkint, Verheyen, De Kegel, Helsen, & Adriaens, 2012).…”
Section: Trade-offs Between Offspring Size and Offspring Numbermentioning
confidence: 99%